Do Phosphate and Cytokinin Interact to Regulate Strigolactone Biosynthesis or Act Independently? - Yoneyama, Kaori; Xie, Xiaonan; Nomura, Takahito; Yoneyama, Koichi (Frontiers in Plant Science, 2020)
Strigolactones (SLs) are essential host recognition signals for both root parasitic plants and arbuscular mycorrhizal (AM) fungi in the rhizosphere, and in planta SLs or their metabolites function as a novel class of plant hormones regulating various aspects of plant growth through crosstalk with other hormones. Although nutrient availability is one of the important factors influencing SL production and exudation, and phosphate (Pi) deficiency significantly promotes SL production and exudation in host plants of AM fungi, it remains elusive how nutrient availability modulates SL production and exudation. Cytokinin (CK), a canonical plant hormone, has extensively been studied as a shoot branching promotor and its biosynthesis is also influenced by mineral nutrients, especially nitrate, indicating that CK might be another key factor affecting SL production and exudation. In the present study, we show that CKs (t-zeatin, benzyladenine, kinetin, and CPPU) applied to hydroponic culture media significantly suppressed SL levels in both root exudates and root tissues of rice plants grown under Pi deficiency. In a split-root system, CK suppressed SL production locally while Pi affected SL production systemically, suggesting that Pi and CK act on SL production independently in rice plants.